Associations of Early Systolic Blood Pressure Control and Outcome After Thrombolysis-Eligible Acute Ischemic Stroke: Results From the ENCHANTED Study. Issue 3 (27th October 2021) - Wang, Xia; Minhas, Jatinder S.; Moullaali, Tom J.; Luca Di Tanna, Gian; Lindley, Richard I.; Chen, Xiaoying; Arima, Hisatomi; Chen, Guofang; Delcourt, Candice; Bath, Philip M.; Broderick, Joseph P.; Demchuk, Andrew M.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: In thrombolysis-eligible patients with acute ischemic stroke, there is uncertainty over the most appropriate systolic blood pressure (SBP) lowering profile that provides an optimal balance of potential benefit (functional recovery) and harm (intracranial hemorrhage). We aimed to determine relationships of SBP parameters and outcomes in thrombolyzed acute ischemic stroke patients. Methods: Post hoc analyzes of the ENCHANTED (Enhanced Control of Hypertension and Thrombolysis Stroke Study), a partial-factorial trial of thrombolysis-eligible and treated acute ischemic stroke patients with high SBP (150–180 mm Hg) assigned to low-dose (0.6 mg/kg) or standard-dose (0.9 mg/kg) alteplase and intensive (target SBP, 130–140 mm Hg) or guideline-recommended (target SBP <180 mm Hg) treatment. All patients were followed up for functional status and serious adverse events to 90 days. Logistic regression models were used to analyze 3 SBP summary measures postrandomization: attained (mean), variability (SD) in 1–24 hours, and magnitude of reduction in 1 hour. The primary outcome was a favorable shift on the modified Rankin Scale. The key safety outcome was any intracranial hemorrhage. Results: Among 4511 included participants (mean age 67 years, 38% female, 65% Asian) lower attained SBP and smaller SBP variability were associated with favorable shift on the modified Rankin Scale (per 10 mm Hg increase: odds ratio, 0.76 [95% CI, 0.71–0.82]; P <0.001 and 0.86 [95% CI, 0.76–0.98]; P =0.025) respectively, but not for magnitude of SBP reduction (0.98, [0.93–1.04]; P =0.564). Odds of intracranial hemorrhage was associated with higher attained SBP and greater SBP variability (1.18 [1.06–1.31]; P =0.002 and 1.34 [1.11–1.62]; P =0.002) but not with magnitude of SBP reduction (1.05 [0.98–1.14]; P =0.184). Conclusions: Attaining early and consistent low levels in SBP <140 mm Hg, even as low as 110 to 120 mm Hg, over 24 hours is associated with better outcomes in thrombolyzed acute ischemic stroke patients. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01422616.